2017
DOI: 10.15835/nbha45210875
|View full text |Cite
|
Sign up to set email alerts
|

AFLP Molecular Identification and Genetic Relationship of Chinese and Japanese Pear Cultivars Grown in Middle European Conditions

Abstract: In this study, 30 genotypes of genus Pyrus (five European cultivars, 16 Asian cultivars, three rootstocks, four interspecific hybrids, one landrace cultivar from Czech Republic ('Krvavka'), Pyrus betulaefolia Bunge. and one intergeneric hybrid (Cydomalus)) were tested using AFLP markers. Twelve primer combinations generated a number of 1251 fragments of which 1064 were polymorphic with an average polymorphism of 85.3%. The dendrogram, created by using the UPGMA method, revealed a distinct genetic relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
6
1
Order By: Relevance
“…The lowest number of variable fragments (47 bands, 64.4%) was observed by the primer combination P174/M307. The average percentage of polymorphic fragments obtained in this study (68.2 %) was lower than that recorded by Wolf et al, (6) who reported 89.5% of the average percentage of polymorphism within pear cultivars. The real reason of this variation is not quite clear.…”
Section: Resultscontrasting
confidence: 85%
See 4 more Smart Citations
“…The lowest number of variable fragments (47 bands, 64.4%) was observed by the primer combination P174/M307. The average percentage of polymorphic fragments obtained in this study (68.2 %) was lower than that recorded by Wolf et al, (6) who reported 89.5% of the average percentage of polymorphism within pear cultivars. The real reason of this variation is not quite clear.…”
Section: Resultscontrasting
confidence: 85%
“…The genus Pyrus (2n = 34 chromosomes), which belong to the tribe Pyreae, subfamily Pomoideae in the Rosaceae family, is widely distributed on six continents particularly in Asia, Europe, and Africa (3,5,1,6). Classically, based on domestication and the geographical distribution, Pyrus species are divided into two major native groups.…”
Section: Introducctionmentioning
confidence: 99%
See 3 more Smart Citations